SEVERAL STRATEGIES TO ABOLISH THE DEATH PENALTY IN DEVELOPING COUNTRY - Diastama Anggita Ramadhan (LAW REFORM, 2018)
The death penalty practice have been an issue in various country. Since the deployment of the ICCPR, there are many country have succesfully abolish the practice of the death penalty or put it in to a moratorium. This international regulation is also affected the developing country. From all over country around the world, several developing countries are still actively use the death penalty as their capital punishment. They argued that executing people have successfully decrease the level of crime in their country. However, it is important to understand that the international regulation are ordered country to abolish the death penalty. This article then will give several strategies for developing country in order to promote the abolishment of the death penalty in all condition.Keyword: Death Penalty; Abolition; Strategy.